Optimizing Fixed-Time Artificial Insemination Efficiency through Co-Synch Techniques in Water Buffaloes (Bubalus bubalis) - Dela Cruz, Carlito F.; Atabay, Edwin C.; Atabay, Eufrocina P.; Maylem, Excel Rio S. (Journal of Buffalo Science, 2026)
The main aim of the study was to optimize the potential of CIDR-CoSynch-hCG protocols developed in water buffaloes. Multiparous animals (163) were assigned to three hormonal treatments. CIDR-Synch-hCG (T1/Control), wherein CIDR and GnRH were given (day 0), prostaglandin (day 7), hCG (day 9), and artificial insemination (AI) was performed twice on day 10. CIDR-CoSynch-hCG-day-9 (T2): Same hormones were given on days 0 and 7, but injection of hCG and AI were concomitantly performed on day 9. CIDR-CoSynch-hCG-day-10 (T3): the same hormones were given on days 0 and 7, but hCG and AI were injected concomitantly on day 10. The size of the pre-ovulatory follicle (POF) at the time of AI was likewise determined to evaluate its influence on pregnancy. The effect of the number of inseminations on pregnancy was determined. Results revealed that pregnancy rates of T1 (43.70%), T2 (43.27%), and T3 (46.07%) were not significantly different (P>0.05). The study demonstrated that simultaneous injection of hCG and AI, either on Day 9 or Day 10 of the CIDR-CoSynch-hCG protocol, is as effective as doing them separately (T1/Control). In addition, large-size (≥12 mm) POF at the time of AI increased pregnancy outcomes (65.52%) compared to medium (41.46%) and small (26.05%) follicles. Meanwhile, twice insemination (51.10%) resulted in significantly higher (P=0.0004) pregnancy rates than single insemination (21.64%). This work identifies key factors and innovative strategies to enhance FTAI implementation in water buffaloes.